Motion-Homogeneous-Based Fast Transcoding Method From H.264/AVC to HEVC - Yuan, Hui; Guo, Chenglin; Liu, Ju; Wang, Xu; Kwong, Sam (IEEE transactions on multimedia, 2017)
With the popularity of high-efficiency video coding (HEVC) standard, a video server usually transcodes a video stream to HEVC for its higher compression ratio. In this paper, a fast H.264/advanced video coding (AVC) to HEVC transcoding method is proposed. In the HEVC encoding procedure, a coding unit (CU), which is a motion-homogeneous block, is first checked based on the analysis of the decoded information from H.264/AVC bit stream. Then, for motion-homogeneous blocks, CU depth and the corresponding prediction unit (PU) mode's early termination strategies are proposed based on the CU size and corresponding prior statistical knowledge. For non-motion-homogeneous blocks, a corresponding PU mode's early termination strategy is also proposed. Experimental results demonstrate the effectiveness of the proposed method.